Teatr niemiecki w pismach i praktyce teatralnej Łesia Kurbasa. Przykład Edypa Króla - Leyko, Małgorzata (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The article attempts to trace the influence of German drama and theatre on the theatrical thought and practice of the Ukrainian director Les Kurbas. His writings provide much evidence that he was very well versed in contemporary German drama and theatre. Using this knowledge, however, he wanted to transform it into his own stage solutions. Kurbas’s artistic independence was shown using the comparative method. The performance of King Oedipus directed by Max Reinhardt and Kurbas is compared. The basic materials come from the extensive edition of Les Kurbas’s theatrical writings in Polish.